PEMANFAATAN SISTEM INFORMASI GEOGRAFI UNTUK ANALISIS POLA SPASIAL-TEMPORAL DISTRIBUSI MAHASISWA BARU UNIVERSITAS COKROAMINOTO PALOPO - Iriansa, Iriansa; Hamzah, Muhammad Akram; Jumardi, Andi (Universitas Muhammadiyah Gorontalo, 2024)
Spatial-temporal information on the new college student amount is of significant importance in planning, strategic decision-making, and managing higher education institutions to increase the number of new college student. Therefore, the role of geospatial technology is needed to assist in the analysis and provision information. This research aims to understand the characteristics of spatial-temporal patterns and clusters in the amount distribution of new UNCP college student from Luwu Regency. The study utilizes secondary data analyzed using GIS techniques. A spatial approach is applied to interpret the results of data analysis, and conclusions are drawn qualitatively. The research findings show a varied distribution of the number of new college student, both spatially and temporally. The spatial distribution pattern tends to be centralized, while the temporal characteristics exhibit three patterns: increasing, fluctuating, and decreasing. Several districts fall into clusters of Potential Areas and Critical Areas that require attention from UNCP for strategic planning and more effective policies to increase the interest of prospective new college student in the future.